Identity Matters: Qatar and Paris Saint-Germain - Thomas Ross Griffin (22590599) (2023)
When Qatar Sports Investments (QSI), an investment group created by the Qatari government, went shopping for a European football club in 2011, few predicted that QSI would turn to France and Paris Saint-Germain (PSG). Even fewer imagined the extent of the change that followed as Qatar’s sports investment body transformed PSG from perennial underachievers into one of Europe’s most glamourous clubs. The team’s success over the past decade has made the Gulf nation a much more visible entity on Europe’s sporting landscape. There has been a swathe of academic literature dedicated to understanding Qatar’s use of football in a soft power context, with the 2022 World Cup at the heart of many of these discussions. Academic work on the relationship between Qatar and PSG is sparse by comparison. While some embrace the identity performance enabled by Qatar’s ownership of PSG with little or no scepticism, others are reluctant to accept PSG, and by proxy Qatar, as part of the social fabric of the West. This study examines QSI’s investment in PSG, which has made the French club synonymous with the Gulf state and has allowed Qatar access to a hegemonic sports culture from which it can perform its national identity overseas. Other Information Published in: Journal of Arabian Studies License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1080/21534764.2024.2356290